Grievances and conspiracy theories as motivators of anti-authority protests - Cubitt, Timothy (Trends & issues in crime and criminal justice, 2024)
This study involved interviews with a sample of individuals who protested in opposition to public health measures introduced during the COVID-19 pandemic. These interviews were analysed to explore the motivations for participating in protest activity. Protesters were motivated by strong personal grievances based on perceived negative experiences and deterioration of their or their family’s personal circumstances. For many respondents, these grievances were shaped by and amplified by adherence to conspiratorial ideologies and sovereign citizen beliefs. The combination of grievances and conspiratorial beliefs fostered mistrust and strong anti-government sentiment. For many, the response by government had steeled their resolve to protest. These findings demonstrate the diverse and sometimes extreme views that can motivate people to participate in protest activity against government authority.